2015
DOI: 10.1371/journal.pone.0135324
|View full text |Cite|
|
Sign up to set email alerts
|

Amniotic Membrane Modifies the Genetic Program Induced by TGFß, Stimulating Keratinocyte Proliferation and Migration in Chronic Wounds

Abstract: BackgroundPost-traumatic large-surface or deep wounds often cannot progress to reepithelialisation because they become irresponsive in the inflammatory stage, so intervention is necessary to provide the final sealing epidermis. Previously we have shown that Amniotic Membrane (AM) induced a robust epithelialisation in deep traumatic wounds.Methods and FindingsTo better understand this phenomenon, we used keratinocytes to investigate the effect of AM on chronic wounds. Using keratinocytes, we saw that AM treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(87 citation statements)
references
References 80 publications
4
82
1
Order By: Relevance
“…Moreover, its relevance is further demonstrated by the fact that AM co‐treatment with TGF‐ß provides increased migration both in MvLu1 and HaCaT cells, although treatment with just TGF‐ß reports mixed results. Interestingly, in line with observations about AM treatment inducing re‐epithelialization of chronic wounds (Alcaraz et al, ; Insausti, Alcaraz, et al, ), previous work in our laboratory has demonstrated that AM is able of attenuating the expression profile of relevant genes involved in cell cycle regulation under TGF‐ß control (Alcaraz et al, ), which resembles how attenuation of TGF‐ß signalling has also been demonstrated to be critical for some tumour cells to escape from cell cycle arrest (Nicolas & Hill, ). In that sense, exacerbated canonical TGF‐ß signalling has been linked to the promotion of skin fibrosis in an intricate process that involves fibroblast, keratinocyte and leucocyte interaction (Andrews, Marttala, Macarak, Rosenbloom, & Uitto, ; Ashcroft & Roberts, ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, its relevance is further demonstrated by the fact that AM co‐treatment with TGF‐ß provides increased migration both in MvLu1 and HaCaT cells, although treatment with just TGF‐ß reports mixed results. Interestingly, in line with observations about AM treatment inducing re‐epithelialization of chronic wounds (Alcaraz et al, ; Insausti, Alcaraz, et al, ), previous work in our laboratory has demonstrated that AM is able of attenuating the expression profile of relevant genes involved in cell cycle regulation under TGF‐ß control (Alcaraz et al, ), which resembles how attenuation of TGF‐ß signalling has also been demonstrated to be critical for some tumour cells to escape from cell cycle arrest (Nicolas & Hill, ). In that sense, exacerbated canonical TGF‐ß signalling has been linked to the promotion of skin fibrosis in an intricate process that involves fibroblast, keratinocyte and leucocyte interaction (Andrews, Marttala, Macarak, Rosenbloom, & Uitto, ; Ashcroft & Roberts, ).…”
Section: Discussionsupporting
confidence: 83%
“…AM was prepared as described in Alcaraz et al (). Briefly, term placenta from healthy donor mothers was obtained from uncomplicated caesarean section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in p-ERK-1/2 and p-p38 expression as well as a functional association between the two have been observed in keratinocytes of psoriatic lesions in humans4244 and in mouse keratinocytes under pruritogenic conditions 45. Furthermore, p-ERK expression is enhanced in human keratinocytes in in vitro models of acute and chronic wounds 46,47. The phosphorylation of ERK can also be induced by pro-algesic factors such as epidermal growth factor 47.…”
Section: Discussionmentioning
confidence: 96%
“…The capacity of HaCaT cells to migrate, proliferate, and close a defined injury area into a confluent monolayer was evaluated by following a previously reported assay with some modifications [30]. Briefly, monolayer cells were scratched vertically with a P1000 pipette tip to create an artificial wound and washed twice with PBS to remove cellular debris.…”
Section: Methodsmentioning
confidence: 99%